Penerapan Strategi Card Sort Terhadap Hasil Belajar IPA - Inekke Oktavianti; Yuni Krisnawati; R Angga Bagus Kusnanto (Journal of Elementary School (JOES), 2023)
This study aims to determine whether the application of the card sort strategy can complete the science learning outcomes of grade V students of SD Negeri 22 Lubuklinggau. The research method used is quasi-experimental. Data collection techniques in research using essay tests. Data analysis techniques with steps: determining the mean and standard deviation, normality test and one-sample test type t test calculated using SPSS 24 calculation. The results of the analysis using the one-sample test t test at a significant level ∝ = 0.05 and dk = 24 showed a p-value value of < 0.05 (0.003 < 0.05) so that it can be concluded that Hₒ was rejected and Hₐ was accepted, meaning that the average science learning outcomes of grade V students of SD Negeri 22 Lubuklinggau after the application of the significant card sort strategy were completed with categories more or equal to 75 (μₒ≥ 75). So it can be concluded that the results of science learning for grade V students of SD Negeri 22 Lubuklinggau after the implementation of the card sort strategy are significantly complete. Keyword: Applicability, Card Sort, Learning Outcomes, Socil Education.